Performance Measurement of Customer Relationship Management Using Scorecard CRM ( Case Study of UKM in Bayat Klaten District ) - Mauidzoh, Uyuunul (Sekolah Tinggi Teknologi Adisutjipto, 2018)
UKM have an important role in helping the economy in society. One of the UKM that is sufficient to help the economy of the community is Batik UKM. The development of UKM is currently receiving serious attention from various circles, including UKM, the natural coloring batik in Bayat District. This study aims to design measuring the performance measurement of Customer Relationship Management in UKM Batik Pewarna Alam in Bayat. In this design data search is done through literature sources and interviews and questionnaire distribution from respondents. From the search results obtained perspectives and also Key Performance Indicators for each perspective. The perspective and indicators that will be included in the CRM Scorecard are determined using the Analytical Hierarchy Process (AHP) method. The perspective in the CRM Scorecard is Customer Knowledge, Customer Value, Customer Interaction and Customer Satisfaction. Where each perspective has indicators in measuring its success.